THE COMPETITIVENESS OF COMMODITIES SEAWEED USING POLICY ANALYSIS MATRIX (PAM) - Jumiati, Elly; Mubarak, Ahmad; Sunny, Khalid (Faculty of Animal and Agricultural Science, Diponegoro University, 2024)
Seaweed products from the city of Tarakan have been traded to outside areas such as Makassar and Surabaya before being exported overseas. This study aims to analyze the competitiveness of seaweed in Tarakan City using the policy analysis matrix (PAM) method. The PAM method is used two main indicators for measuring competitiveness, namely the Private Cost Ratio (PCR) as an indicator of competitive advantage and the Domestic Resource Cost Ratio (DRCR) which is an indicator of comparative advantage. The results showed that seaweed in Tarakan City had a PCR value of 0.37 and a DRC of 0.08, the private profit (PP) obtained was Rp 6,444,319 financially has a competitive advantage at the business level farmer. Social profit (PS) of Rp 30,386,901 economically or the economy as a whole has a comparative advantage which means efficient use of resources. The impact of government policies on the output of seaweed cultivation is not protective with an NPCO value of 0.34. The impact of government policies on seaweed cultivation inputs is not protective with an NPCI value of 1.29, meaning that farmers have not received positive incentives from the current input subsidy policy. The EPC value of 0.31 means that the overall impact of government policies on input-output is protective and provides positive incentives to farmers, but is still relatively weak and very vulnerable if policy changes occur. The regional government is expected to provide protection to seaweed cultivators in the form of setting costs for purchasing seaweed and also to strictly supervise cartel practices in the seaweed trading system.